Remote spinal epidural hematoma after spinal anesthesia for caesarean section - Vilaça, MJ (2016)
In the last few decades there has been a widespread of the use of central neuraxial blockages (CNB) in obstetric patients. The complications from the CNB range from the bothersome to the crippling and life-threatening. Spinal epidural hematoma (SEH) is one of such severe complications. A 29-year-old pregnant woman at term, ASA II, was proposed for a caesarean section after inadequate progression of labour. Spinal anesthesia was administered and surgery was uneventful. The patient recovered from the motor and sensitive blockage but, twelve hours after the procedure, she started complaining of paresthesia over the lower limbs that progressed to paraplegia. An urgent magnetic resonance revealed a dorsally located SEH extending from D7 to D9, remote from the site of needle puncture. The patient was transferred and an emergency laminectomy and evacuation of the hematoma was conducted. One year after the event she remained with neurological deficits.